Pengembangan Media Majas Puzzle Quest Berbasis Cooperative Learning Tipe Make a Match pada Mata Pelajaran Bahasa Indonesia untuk Meningkatkan Kemampuan Kolaborasi Siswa Kelas V SDN 47 Kodo Kota Bima - Nur Raehani; Muh. Rijalul Akbar; Muhammad Zia Ulhaq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study's objective is to determine the feasibility, practicality, and effectiveness of majas puzzle quest based cooperative learning tipe make a match in Indonesian language learning to improve the collaboration skills of grade V students of SDN 47 Kodo, Bima City. The ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation, is used in this study in conjunction with the Research and Development (R&D) approach. Data were collected through media and material expert validation questionnaires, teacher and student response questionnaires, and student collaboration skills observation questionnaires. The instruments were analyzed descriptively quantitatively. The media expert validation results showed an average score of 93.33% (very feasible category), and the material expert validation results amounted to 97.14% (very feasible category). Teacher responses showed an average score of 80% (practical category), while student responses amounted to 85.72% (very practical category). The results showed that majas puzzle quest based cooperative learning tipe make a match was effectively used in learning, with an increase in the average score of students' collaboration skills from 44.27% in the medium category to 62.02% in the high category